IMPLEMENTASI KEBIJAKAN LAYANAN BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN DI PUSKESMAS AMPIBABO KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG - Efendi, Moh.; Kurnia, Intam; Ferianto, fiki (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to determine the implementation of BPJS (Social Security Administration) Health service policy at Ampibabo Health Center, Ampibabo District, Parigi Moutong Regency. The researcher conducted the research using qualitative methods, while the type of research used in this study is descriptive research. The type of data consists of primary data and secondary data. Determination of informants using the Purposive technique. In addition, the data collection technique in this study through library research and field research with observation, interview, and documentation activities. The data analysis method according to Huberman (2014), data condensation, data display, and conclusion drawing and verification. This study uses the policy implementation theory put forward by Edward III which consists of 4 aspects, namely communication, resources, disposition, and bureaucratic structure. From the results of the study, the researcher concluded that the implementation of the BPJS (Social Security Administration) Health service policy at the Ampibabo Health Center, Ampibabo District, Parigi Moutong Regency has not been implemented optimally, this can be seen after going through the research process, with many problems that still occur, such as in the communication aspect, it is still not running optimally. Although communication between program implementers has been going well. The distribution of all information related to the program to the target group, in this case the community, is considered to be still not running optimally. Then from the aspect of resources, it is still not running optimally, this is caused by inadequate human resources, the Ampibabo Health Center does not have specialist doctors, and in addition, supporting facilities in the implementation of the BPJS (Social Security Administration) Health service policy at the Ampibabo Health Center are still inadequate.